Do People Value Recorded Music? - Marshall, Lee (Cultural sociology, 2019)
How much do the majority of people value music, and can or should that level of value be reflected in music’s economic value? The dramatic decline in the economic value of recorded popular music in the 21st century has prompted much debate about music being ‘devalued’ and the perceived ‘value gap’ between music’s socio-cultural and economic values. Using the economic decline of recorded music as a springboard, this article takes a different approach, however. It offers a theoretical analysis of popular music consumption practices organised thematically in terms of ‘music as object’ (focusing on the social values generated and perceived by recorded music artefacts) and ‘music as sound’ (focusing on the way that most contemporary musical experiences are characterised by music being background sound or accompaniment). Overall, the argument is that ‘music’ may not be as culturally valued by people as is commonly assumed. The way that music operates as a low-value entity to many people is perhaps reflected in the cultural and economic contours of the digital music industry, though they are not caused by digitisation per se.